Evaluación de la cobertura vegetal en bofedales altoandinos en función de la napa freática y precipitación utilizando imágenes de satélite - Javier Silva, Luz Alexandra (2021)
The study area included the Minas Corral wetland; Ayacucho, where the relationship between precipitation, groundwater monitoring, and the identification of vegetation cover variation was determined through NDVI (standardized vegetation index), with the use of remote sensors such as satellites, which facilitate the collection of information in a period of time. The precipitation data were obtained from the Apacheta meteorological station, located at 4 150 masl, in the district of Paras, Cangallo province of the Ayacucho region, where the information was validated in monthly periods. To obtain the information on groundwater, 31 samples were taken at observation points (piezometers), randomly and for the visualization of the monthly variation of vegetation cover images of the Landsat 8 satellite were used. The relationship between the defined parameters was analyzed, from the spatial point of view, where the monthly correlations between NDVI, precipitation and groundwater were established, the results obtained indicate that there is a high and inverse correlation of 97% for the variables (Vegetation area and groundwater) and direct 49% (vegetation area and precipitation) and the results obtained by the test of independence between variables verify our hypothesis, Therefore, it is concluded that the relationship between the variables (groundwater and precipitation) conditions the extension and a type of plant formation, which vary in composition by seasonality.